2006
DOI: 10.1029/2005jb004032
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical analysis of strain localization in a ductile detachment zone

Abstract: [1] At the latitude of the Thor-Odin dome (British Columbia) the Columbia River Detachment defines the eastern margin of the Shuswap metamorphic core complex and localizes in a 1 km thick muscovite-bearing quartzite mylonite. We present a combined 40 Ar/ 39 Ar, (micro)structural, and oxygen isotope study of the deformation history in the detachment and evaluate the spatial and temporal relationships between microstructure formation and localization of strain. Ar/ 39 Ar geochronology from different levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 79 publications
5
91
0
Order By: Relevance
“…The "classical" hydrodynamic model for MCCs and associated detachments corresponds to (Reynolds and Lister, 1987): i) an upper plate with hydrostatic surface-derived fluid pressure, free convective cells, high fluid-rock ratios under high differential stresses; ii) a lower plate with supra-hydrostatic metamorphic/magmatic fluid pressure, low fluid-rock ratios under low differential stresses. It is however well established that surface-derived fluids may deeply percolate at the brittle-ductile transition along detachment zones (Fricke et al, 1992;Kerrich and Rehrig, 1987;Mulch et al, 2006) triggering abnormal advective thermal gradients able to drastically refrigerate exhuming footwall rocks (Morrison et al, 1998). As they reach the top of the ductile crust, those surface-derived fluids are supposed to localize strain in a reaction-enhanced weakening front , Gueydan et al, 2003.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The "classical" hydrodynamic model for MCCs and associated detachments corresponds to (Reynolds and Lister, 1987): i) an upper plate with hydrostatic surface-derived fluid pressure, free convective cells, high fluid-rock ratios under high differential stresses; ii) a lower plate with supra-hydrostatic metamorphic/magmatic fluid pressure, low fluid-rock ratios under low differential stresses. It is however well established that surface-derived fluids may deeply percolate at the brittle-ductile transition along detachment zones (Fricke et al, 1992;Kerrich and Rehrig, 1987;Mulch et al, 2006) triggering abnormal advective thermal gradients able to drastically refrigerate exhuming footwall rocks (Morrison et al, 1998). As they reach the top of the ductile crust, those surface-derived fluids are supposed to localize strain in a reaction-enhanced weakening front , Gueydan et al, 2003.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Coney and Harms, 1984;Gans, 1997;Gans and Miller, 1985;Perchuk and Gerya, 2011;Reynolds and Lister, 1987). Fluid flow and metamorphic reactions also concentrate along them (Gottardi et al, 2011;Holk and Taylor, 2000;Morrison and Anderson, 1998;Mulch et al, 2006). As a result, detachments are also reaction fronts where thermodynamic re-equilibration of metastable assemblages is catalyzed by the infiltration of fluids in the high strain a b c Fig.…”
Section: Geological Evidence For Fluid-limited Phase Transitions: In mentioning
confidence: 99%
“…Yet, several authors have shown that during active extension, surface-derived fluids can penetrate in the brittle upper crust through the arrays of normal faults that spread down to the detachment footwall (Famin et al, 2004;Gottardi et al, 2011;Gottardi et al, 2013;Morrison and Anderson, 1998;Mulch et al, 2006). Hence, the meteoric fluid down-flows can mix up with the metamorphic fluid circulation in the brittle-ductile mylonitic shear zones (Ferry, 1994;Fusseis and Handy, 2008;Manchtelow and Pennacchioni, 2004;Marquer and Burkhard, 1992;Oliot et al, 2014).…”
Section: Fluid and Layer Bendingmentioning
confidence: 99%
“…In this paper, we investigate these potential models along a well-exposed low-angle detachment in the European Alps, combining detailed geochronology and thermochronology with structural, petrological and chemical analyses. Many studies have already used thermochronology to investigate the timing and rate of exhumation on low-angle detachments [e.g., Foster et al, 1993;Grasemann and Mancktelow, 1993;Wells et al, 2000;Vanderhaeghe et al, 2003;Brichau et al, 2006;Mulch et al, 2006], generally based on the concept of cooling ages for different mineral and isotopic systems [e.g., Wagner et al, 1977]. In contrast, absolute ages of deformation are rather difficult to obtain but have been acquired by dating neocrystallized synkinematic minerals (usually white mica) from specific structural sites, such as strain shadows, [Müller et al, 2000a] or from retrograde phyllonitic shear zones [Dunlap, 1997;Challandes et al, 2003Challandes et al, , 2008Kirschner et al, 2003;Mulch and Cosca, 2004;Mulch et al, 2005;Rolland et al, 2008;Rolland et al, 2009].…”
Section: Introductionmentioning
confidence: 99%